Criminal background and job performance - Dylan Minor; Nicola Persico; Deborah M. Weiss (IZA Journal of Labor Policy, 2018)
Job applicants with criminal records are much less likely than others to obtain legitimate employment. Recent efforts to address this problem include campaigns to persuade employers to hire applicants with a record voluntarily and legislation such as Ban the Box laws. The success of any remedial strategy depends on whether employer concerns are founded on an accurate view of how employees with a criminal background behave on the job if hired. Little empirical evidence now exists to answer this question. This paper attempts to fill this gap by examining firm-level hiring practices and worker-level performance outcomes. Our data indicate that individuals with criminal records have a much longer tenure and are less likely to quit their jobs voluntarily than other workers. Some results, however, differ by job: sales employees with a criminal record have a higher tendency than other workers to leave because of misconduct, while this effect is smaller and less significant for customer service workers. By examining psychometric data, we find evidence that bad outcomes for sales people with records may be driven by job rather than employee characteristics. We find some evidence that psychometric testing might provide a substitute for the use of criminal records, but that it would not in our own sample.
Keywords: K14; J24; J78; 330; Criminal records; Discrimination; Personnel economics; Job performance